Investigation of a traumatic psychosis subgroup: a cluster analysis of an antipsychotic free cohort. Issue 4 (2nd October 2019) - Stevens, Lucy H.; Turkington, Douglas; Drage, Laura; Morrison, Tony; Muncer, Steven; Spencer, Helen M.; Dudley, Robert
ABSTRACT: Childhood trauma is linked to an increased risk of developing psychosis in adulthood. The extent and severity of trauma experienced is known to correlate with the intensity or presence of specific psychotic symptoms. The relative impact of types of abuse and neglect (sexual, physical, emotional) is unknown. Cluster analysis was used to create natural groupings of similarity based on Childhood Trauma Questionnaire Scores (CTQ) in a sub-sample of 51 anti-psychotic-free patients with diagnoses of Schizophrenia Spectrum Disorders from the ACTION trial. The derived clusters were compared on the Positive and Negative Syndrome Scale (PANSS) scores. Two clusters emerged: one characterized by abuse and the other by neglect. The abuse group was found to have significantly higher positive symptoms scores (p < 0.05). This is the first investigation of this concept in an un-medicated cohort that distinguished between trauma types using natural groupings in the data, and therefore, a more ecologically valid means of exploring the existence of a traumatic psychosis subgroup.